AI in Healthcare: Time-Series Forecasting Using Statistical, Neural, and Ensemble Architectures - Kaushik, Shruti; Choudhury, Abhinav; Sheron, Pankaj Kumar; Dasgupta, Nataraj; Natarajan, Sayee; Pickett, Larry A.; Dutt, Varun (Frontiers in Big Data, 2020)
Both statistical and neural methods have been proposed in the literature to predict healthcare expenditures. However, less attention has been given to comparing predictions from both these methods as well as ensemble approaches in the healthcare domain. The primary objective of this paper was to evaluate different statistical, neural, and ensemble techniques in their ability to predict patients’ weekly average expenditures on certain pain medications. A statistical auto-regressive integrated moving average (ARIMA) model, a multi-layer perceptron (MLP) model, a long short-term memory (LSTM) model, and an ensemble model combining predictions of the ARIMA, MLP, and LSTM models were calibrated to predict the expenditures on two different pain medications. In the MLP and LSTM models, we compared the influence of shuffling of training data and dropout of certain nodes in layers during training. Results revealed that the ensemble model outperformed the ARIMA, MLP, and LSTM models across both pain medications. In general, not shuffling the training data and adding the dropout helped the MLP models and shuffling the training data and not adding the dropout helped the LSTM models across both medications. We highlight the implications of using statistical, neural, and ensemble methods for time-series forecasting of outcomes in healthcare domain.